2015
DOI: 10.1007/s11012-015-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Modified geometry of spur gear drives for compensation of shaft deflections

Abstract: One of the greatest concern of spur gears is the edge contact of tooth surfaces that is caused by misalignment of the gear drive. Such a misalignment is caused partially by the deflections of the shafts where the gears are mounted. As a result of the edge contact a non favorable condition of bearing contact is achieved, providing a high level of contact and bending stresses. An intensive research and many practical solutions have been directed to modify the gear tooth surfaces in order to avoid edge contact. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The appropriate adoption of the necessary coordination systems and the finite element mesh [13,22,23] is the main important determining parameters for the TCA analysis [7,8,9,13]. For this analysis three coordination systems have been adopted [9,10]:…”
Section: Tca Analysis Of the Gear Pairsmentioning
confidence: 99%
“…The appropriate adoption of the necessary coordination systems and the finite element mesh [13,22,23] is the main important determining parameters for the TCA analysis [7,8,9,13]. For this analysis three coordination systems have been adopted [9,10]:…”
Section: Tca Analysis Of the Gear Pairsmentioning
confidence: 99%
“…Such data were derived in [15] for spiral bevel and hypoid gears produced either by face-milling or facehobbing. Determination of blank data from basic data such as the power to transmit, the gear ratio, the pinion speed, the shaft angle, and the quality of gears, can be based as well on the application of Standard ANSI/AGMA 2005-C96 [8] for the case of spiral bevel gears produced through the cyclo-palloid system.…”
Section: Analytical Determination Of Pinion and Gear Basic Machine-tomentioning
confidence: 99%
“…Regarding the position of the pinion (or the gear) in the cutting machine, the basic machine-tool settings are set as follows (see [15] to identify nomenclature and settings):…”
Section: Analytical Determination Of Pinion and Gear Basic Machine-tomentioning
confidence: 99%
See 1 more Smart Citation
“…However, no research has been found on how to avoid the occurrence of the hub tooth tip edge contact with the sleeve tooth root flank and the sleeve tooth tip edge contact with the hub tooth root flank. Edge contact results in unexpected early failure of a gear transmission because of highly concentrated contact stress generated between the tip of one member and the root flank of the other (Litvin et al, 2003;Gonzalez-Perez et al, 2015;Fuentes-Aznar et al, 2017;Guo et al, 2019). And, the same is true for the crown gear coupling.…”
mentioning
confidence: 98%